TRANSPARENT ASSESSMENT MODEL IN ARCHITECTURE DESIGN STUDIO: EASTERN MEDITERRANEAN UNIVERSITY AS CASE STUDY - Hassanpour, Badiossadat; Ani, Adi Irian Che (Open House Int, 2015)
Art and architecture are multidisciplinary fields with complicated assessments that, similar to the teaching and the learning process, are inconsistent with common assessment models. During submission, the presence of jurors, who have different approaches and standards for evaluating design projects, makes this issue more complicated. Numerous assessment and grading models are being used in architecture departments around the world. Some of these methods are based on the experiences of instructors from their lives as students, whereas some are based on university systems. Grading policies seem to be clear in most fields, but when the object of grading is an artistic product with different levels to be assessed and graded, the issue becomes more complex. This observation is especially true in the case in which quality is given a numerical grade. The nature of skills that students are expected to develop and that are going to be assessed is often subjective. Such skills include invention, problem solving, and presentation. Problems of reliability, personal criterion, and unique perceptions lend difficulty in assessing such skills using traditional methods. This research suggests that a criteria-based assessment and grading model is a more effective model in promoting student learning, making assessment and grading less complex and more explicit. The effectiveness and reliability of the proposed and implemented criteria-based grading system has been tested at Eastern Mediterranean Universily using distributed questionnaires and a Rasch measurement system.
Keywords: Architecture Design Studio; Grading and Assessment; Criteria; Rasch System